Fire performance of non-loadbearing light steel framing walls – numerical simulation - Piloto, P.A.G. (2017)
Light steel frame and prefabricated panels are widely used in non-load-bearing walls, with direct application to steel framed buildings. The fire resistance is usually provided by one or more layers of fire protection materials and the assembly is able to achieve a fire resistance in accordance to technical regulations. Many different types of board materials can be used, including gypsum-based boards. This investigation evaluates the behaviour of the cavity, with and without insulation material. The finite volume method is applied to perform the thermal analysis of the wall taking into account the fluid effect in the cavity. The finite element method is applied to perform the thermal analysis of the wall with insulation material in the cavity. The fire resistance is compared for both models (with and without insulation) and a new simple formula is proposed for the temperature evolution in the cavity zone. Some insulant materials can reduce the fire resistance of the wall, taking into to consideration the insulation criterion.